New optical hybrid electric and magnetic B-2-phase with Landau Lifshitz approach - Körpınar, Talat; Körpınar, Zeliha (Taylor & Francis Ltd, 2021)
In this manuscript, we obtain different characterization for hybrid electromagnetic flow B-2-density of B-2-hybrid phase by new frame in ordinary space. Thus, we define new optical conditions of B-2-electromagnetic B-2-phase with optical fields. We obtain electromagnetic Lorentz B-2-flux for optical fields with Landau Lifshitz method. Finally, electromagnetic B-2-phase of B-2-surface are demonstrated in optical magnetic B-2-surfaces by optical geometric results for hybrid Landau Lifshitz method.
Keywords: Hybrid frame; optical hybrid physics; hybrid Landau Lifshitz approach; hybrid electric and magnetic flow density; Equation; Curves; Evolution; Solitons; Fiber; Geometry; Flows; Phase; Wave